A COMPARATIVE STUDY OF STRENUOUS WORKING CONDITIONS IN GOVERNMENT AND PRIVATE SCHOOLS IN BIHAR - Ansari, Md Ansar Alam (International Journal of Research -GRANTHAALAYAH, 2026)
This research explores the physical and environmental demands placed on educators within Bihar’s public and private academic sectors. Utilizing the "Strenuous Working Conditions" dimension of Srivastava and Singh’s Occupational Stress Index (OSI), the study surveyed a sample of 304 teachers from the Southwestern districts of Bihar, including Patna, Bhojpur, Buxar, Rohtas, and Kaimur. The empirical findings demonstrate a clear disparity in stress triggers between the two sectors. Specifically, educators in private institutions reported markedly higher stress levels, driven by prolonged instructional hours, intensive workloads, and heightened physical exhaustion. These insights highlight a critical necessity for institutional reforms aimed at mitigating workplace strain and fostering better mental health among teaching professionals.